Risk of Renal Injury After the Use of Polyethylene Glycol for Outpatient Colonoscopy: A Prospective Observational Study. Issue 10 (November 2019) - Cheng, Chi-Liang; Liu, Nai-Jen; Tang, Jui-Hsiang; Kuo, Yen-Lin; Lin, Cheng-Hui; Lien, Jau-Min; Tsui, Yi-Ning; Lee, Bai-Ping; Hung, Hsiang-Ling
Abstract : Goal: The goal of this study was to estimate the risk of renal injury after the use of 3-L polyethylene glycol (PEG) before outpatient colonoscopy. Background: Population-based studies showed that the use of PEG was associated with renal injury, but this association has not been confirmed by prospective study. Study: Patients ≥40 years of age with an estimated glomerular filtration rate ≥30 mL/min were screened for enrollment. Laboratory data were collected before, during, and after the colonoscopies. Patients with a ≥30% increase in baseline serum creatinine levels were followed until a peak level was detected. Renal injury included acute renal dysfunction (ARD) and acute kidney injury (AKI), defined as a 30% to 49% increase and ≥50% increase in creatinine levels compared with the baseline, respectively. Results: A total of 1163 patients (mean age, 55.7 y) completed the study. Baseline and first postcolonoscopy laboratory data were obtained an average of 17.0 days before and 17.3 days after the colonoscopies were performed, respectively. Renal injury was identified in 32 patients; 26 patients (2.2%) had ARD, and 6 patients (0.5%) had AKI. All patients with renal injury recovered fully during follow-up. In the subgroup analysis, the use of nonsteroidal anti-inflammatory drugs (NSAIDs) before colonoscopy was statistically associated with the development of AKI (odds ratio, 6.5; 95% confidence interval, 1.2-35.5; P= 0.03). Conclusions: This prospective study showed that the use of PEG was associated with a small risk of renal injury. NSAIDs use was statistically associated with AKI in the context of colonoscopy for which PEG was used for bowel preparation.